2020
DOI: 10.1021/acs.inorgchem.0c01731
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Synthesis and Magnetocaloric Effect in AlFe2B2

Abstract: A promising magnetic refrigerant, AlFe 2 B 2 , has been prepared for the first time by microwave (MW) melting of a mixture of constituent elements. For comparison, samples of AlFe 2 B 2 have been also prepared by arc-melting, traditionally used for the synthesis of this material, and by induction (RF) melting, which was used in the very first report on the synthesis of AlFe 2 B 2 . Although an excess of Al has to be used to suppress the formation of ferromagnetic FeB, the other byproduct, Al 13 Fe 4 , is easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Among the MAB compounds, Fe 2 AlB 2 exhibits interesting magnetic properties, including magnetic anisotropy and room-temperature magnetism, making it a promising candidate for magnetic refrigeration applications. It has been previously shown that Fe 2 AlB 2 demonstrates itinerant magnetism. The saturation magnetization at temperatures ≤50 K ranges from 0.7 to 1.60 μ B /Fe atom, , while the Curie temperature, T C , falls within the range of 272 to 320 K, , indicating a second-order magnetic transition around room temperature from a low-temperature ferromagnetic state to a high-temperature paramagnetic state. ,, Moreover, bulk Fe 2 AlB 2 exhibits soft magnetic behavior with negligible remanence and coercivity. ,, However, due to its highly anisotropic crystal structure, Fe 2 AlB 2 single crystals display pronounced anisotropic magnetic properties. Fe 2 AlB 2 exhibits a reversible MCE near room temperature, characterized by a second-order magnetic transition, without experiencing cracking or hysteresis losses. ,,, The isothermal entropy change Δ s T and the indirectly determined adiabatic temperature change Δ T ad in Fe 2 AlB 2 are reported to be in the range of 1.3–4.4 J/(kg K) ,,,,,, and 1.0–1.8 K , at a magnetic field change of 2 T, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among the MAB compounds, Fe 2 AlB 2 exhibits interesting magnetic properties, including magnetic anisotropy and room-temperature magnetism, making it a promising candidate for magnetic refrigeration applications. It has been previously shown that Fe 2 AlB 2 demonstrates itinerant magnetism. The saturation magnetization at temperatures ≤50 K ranges from 0.7 to 1.60 μ B /Fe atom, , while the Curie temperature, T C , falls within the range of 272 to 320 K, , indicating a second-order magnetic transition around room temperature from a low-temperature ferromagnetic state to a high-temperature paramagnetic state. ,, Moreover, bulk Fe 2 AlB 2 exhibits soft magnetic behavior with negligible remanence and coercivity. ,, However, due to its highly anisotropic crystal structure, Fe 2 AlB 2 single crystals display pronounced anisotropic magnetic properties. Fe 2 AlB 2 exhibits a reversible MCE near room temperature, characterized by a second-order magnetic transition, without experiencing cracking or hysteresis losses. ,,, The isothermal entropy change Δ s T and the indirectly determined adiabatic temperature change Δ T ad in Fe 2 AlB 2 are reported to be in the range of 1.3–4.4 J/(kg K) ,,,,,, and 1.0–1.8 K , at a magnetic field change of 2 T, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its excellent performance in the alkaline electrocatalytic OER, AlFe 2 B 2 is not stable under acidic conditions. In contrast, many ternary phosphides with related layered structures (Figure b) are known to exhibit high stability toward acids . Building on this knowledge, we have decided to explore the use of such structures in both acidic and alkaline water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, AlFe 2 B 2 has attracted much attention for future refrigeration with earthabundant elements, room-temperature magnetic transitions, and strong magnetocrystalline anisotropy energy. [17][18][19][20][21] AlFe 2 B 2 has an orthorhombic layered crystal structure with a space group Cmmm as depicted in Figure 1. The Fe and B layers form a zigzag chain in the ac plane.…”
Section: Introductionmentioning
confidence: 99%